단층촬영법을 이용한 느티나무, 팽나무, 은행나무 노거수의 건강도 측정 - 신현수; 김민영; 전형국; 유지호; 김종갑; Hyun-Su Shin; Min-Young Kim; Hyeong-Guk Jeon; Jong-Kab Kim (농업생명과학연구, 2017)
느티나무, 팽나무, 은행나무 노거수를 대상으로 수간 내부 건강도 단층촬영을 통해 수목의 내부 피해 도를 조사하였다. 단층촬영 결과, 전반적으로 수간 내부의 건강부위 비율은 팽나무>느티나무>은행나무 의 순으로 나타났고, 부후부위는 은행나무>느티나무>팽나무의 순으로 나타났으며, 공동부위는 은행나 무>느티나무>팽나무의 순으로 나타났다. 은행나무의 경우 외관상으로는 공동부위가 나타나지 않았지만 내부적으로는 부후가 진행된 수목도 있었다. 공동부위의 증가로 수간 부러짐 등의 피해가 나타날 수 있 으므로 수간 내부 단층촬영을 통해 내부 부후 상황을 정밀하게 조사·분석함으로써 노거수의 생육상태 를 파악할 수 있으며, 내부단층촬영은 노거수 보호관리에도 응용될 수 있을 것이다. This study was investigated to the internal risk of old trees of Zelkova serrata, Celtis sinensis and Gingo biloba by internal tomography. The proportion of healthy area of trunk was generally high in order of Celtis sinensis, Zelkova serrata and Gingo biloba. The proportion of infection area of trunk was generally high in order of G. biloba, Z. serrata and C. sinensis. The proportion of cavity area of trunk was generally high in order of G. biloba, Z. serrata and C. sinensis. In the case of G. biloba, it did not show the indication of cavity part externally, but there was the system of the internal risk. The old trees are apt to be broken and fallen the trunk by increase in the cavity area. Therefore, it is necessary to sean the internal risk by tomography and this internal tomography can be applied to conservation and management of the old trees.